Optimal Monetary Policy and Stock-Prices Dynamics in a Non-Ricardian DSGE Model - Salvatore Nisticò (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2011)
In a DSGE model with non-ricardian agents, a' la Blanchard-Yaari, stock-price fluctuations affect the dynamics of aggregate consumption through wealth effects. This wealth effects can be characterized as an additional dynamic distortion with respect to the social planner allocation, related to the cross sectional consumption dispersion that the decentralized allocation implies. By exploiting the specific cross-sectional distribution that the model implies for individual financial wealth, this paper derives the welfare criterion consistent with this economy, and shows that it features an additional target besides output-gap and price stability: financial stability. The ultimate implication is that price stability is no longer necessarily optimal, even absent cost push shocks. Given the quadratic form of the welfare criterion, some fluctuations in output and inflation will be optimal as long as they reduce the volatility of financial wealth.
Keywords: E12; E44; E52; 330; Monetary Policy; DSGE Models; Stock Prices; Wealth Effects